SHCBP1 drives tumor progression in triple-negative breast cancer - Wang, Huiling; Dai, Huijuan; Zhou, Liheng; Lin, Yanping; Yin, Wenjin; Lu, Jingsong (Frontiers in Oncology, 2025)
BackgroundsTriple-negative breast cancer (TNBC) represents the most aggressive breast cancer subtype. The limited treatment options underscore the urgent need to explore novel molecular targets to combat TNBC progression. This study investigates the oncogenic functions of SHCBP1 in TNBC.Materials and methodsBulk RNA-seq and single-cell sequencing (scRNA-seq) data for TNBC samples were acquired from the Cancer Genome Atlas (TCGA) dataset and GSE161529, respectively. SHCBP1 expression at the mRNA and protein levels was compared between TNBC and normal breast tissues. The prognostic significance of SHCBP1 in TNBC was assessed using Kaplan–Meier analysis. The potential biological functions of SHCBP1 were explored through gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and gene set enrichment analysis (GSEA). Immunofluorescence was utilized to determine the subcellular localization of SHCBP1 during cell division. Quantitative PCR (qPCR) and western blotting were employed to measure SHCBP1 expression in breast cancer cell lines. Subsequently, the impact of SHCBP1 on TNBC cell proliferation and migration was evaluated in vitro. Finally, scRNA-seq analysis was conducted to characterize SHCBP1 expression patterns at the single-cell resolution.ResultsSHCBP1 is markedly upregulated in TNBC tissues, and its overexpression is associated with poorer survival outcomes. Functional enrichment analysis reveals that SHCBP1-related genes are significantly enriched in pathways involved in cell-cycle regulation and DNA damage response. In vitro studies demonstrate that SHCBP1 enhances TNBC cell proliferation and migration. The scRNA-seq analysis displays the cell clusters in which SHCBP1 is primarily expressed. Cancer epithelial cells exhibiting higher SHCBP1 expression display stronger interactions with stromal cells in the tumor microenvironment.ConclusionsThis study elucidates the critical role of SHCBP1 in TNBC progression, highlighting its potential as a therapeutic target. These findings provide a foundation for further exploration of SHCBP1 in TNBC treatment strategies.